ANALISIS KOMPARASI PERAN WANITA TANI DALAM USAHATANI JAGUNG SERTA PANDANGAN WANITA TANI TERHADAP JAGUNG HIBRIDA DI DESA PAKAAN LAOK DAN DESA DUKO TAMBIN - Salsadyra, Vaundrawati Dheananda; Sugiarti, Teti; Arifianti, Nurul (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2021)
This study aims to determine 1) the differences in the roles of women farmers in maize farming in Pakaan Laok Village and Duko Tambin Villages 2) the differences in the views of women farmers in Pakaan Laok and Duko Tambin villages on hybrid mize. The selection of the research location was carried out using purposive sampling technique with by considering that Pakaan Laok Village and Duko Tambin Village had advantages on different sides. The study was conducted from September to November 2021. The study used the census method and data analysis was carried out using qualitative descriptive analysis. The results showed that the role of women farmers in maize farming in Pakaan Laok Village was high compared to the role of women farmers in Pakaan Laok Village. The view of women farmers in Duko Tambin Village on hybrid maize is better than that of women farmers in Pakaan Laok Village.